Development of in-situ electro-generated chlorine leaching and its application to the leaching of platinum. Issue 3 (4th July 2022) - Kim, Min-Seuk; Kim, Rina; Chung, Kyeong-Woo; Lee, Jae-Chun
ABSTRACT: An in-situ electro-generated chlorine leaching with a closed recycling unit of unconsumed gas was developed for precious metal dissolution and applied to the leaching of platinum from a spent automotive catalyst containing 0.13 wt% Pt. Cathodic current in a cathodic compartment of the chlorine generation cell reduces the unconsumed chlorine gas into chloride ions for further chlorine generation. The electro-reduction efficiency was 99.4% in alkaline 2 M NaCl solution, whereas 80.8% in 35% HCl solution at 0.62 mmol min −1 supply rate of unconsumed chlorine gas. The 98.3% platinum from the spent automotive catalyst leached without discharging the unconsumed chlorine gas into the air at 100 g L −1 solid/liquid ratio and 80°C in a 7 M HCl solution. Increasing the solid/liquid ratio to 400 g L −1 drastically decreased the leaching percentage to 16.5% in 90 minutes by possible adsorption of leached Pt to the porous surface of the automotive catalyst carrier.